عصرِ حاضر میں مثالی نظامِ حکومت کا قیام اور حکمتِ عملی: اسلامی تعلیمات کی روشنی میں ایک مطالعہEstablishment and Strategy of the Ideal System of Government in Cotemporary World: A Study in the Light of Islamic Teachings (Al-Qamar, 2021)
Good Governance is basic subject of Islam. Islam has given comprehensive principles regarding peace, protection of public rights and social prosperity. Another an important aspect of Islam is that strategy of Good Governance presented for making stability. Social stability totally depends on strategy of Good Governance. Without comprehensive strategy we cannot protect our society and also can not address contemporary issues prevailing in the society in the shape of extremism, poverty and injustice. Development of strategy relating Good Governance is dire need of the time.
Keywords: Ideal System; Cotemporary World; Islamic Teachings